STRATEGIES OF DIGITALIZATION IN THE CONTEXT OF BUSINESS DIGITAL TRANSFORMATION: TRENDS AND INNOVATIONS - KUSHCH, Anastasiia; LATYSHEV, Kostiantyn (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article examines the significance of strategic management in fostering the growth and competitiveness of enterprises in today’s rapidly evolving business environment. The study outlines the essential tools, stages, and approaches for implementing strategic management, emphasizing its role in shaping sustainable competitive advantages in the face of global challenges. A key focus of the article is the analysis of the flexibility and adaptability required in strategic planning, particularly in response to changing market conditions, technological advancements, and resource limitations. The research underscores how strategic management enables businesses to optimize resource allocation, streamline operations, and align their objectives with long-term goals to achieve superior performance. Furthermore, the article discusses the barriers that hinder effective strategic management, such as resistance to change, lack of alignment within teams, and resource constraints. It also provides actionable recommendations for overcoming these obstacles through leadership, innovation, and continuous improvement. Overall, the article concludes that strategic management is a fundamental driver of organizational resilience and success in the modern economy. By adopting a strategic approach, companies can better navigate uncertainties, seize growth opportunities, and maintain their competitiveness in an increasingly complex global market.
Keywords: strategic management; enterprise strategy; enterprise competitiveness; strategic development; resource optimization